1999
DOI: 10.1016/s1074-7613(00)80023-0
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Differences in T Cell Receptor Binding of Agonist and Antagonist Ligands

Abstract: The kinetics of interaction between TCR and MHC-peptide show a general relationship between affinity and the biological response, but the reported kinetic differences between antigenic and antagonistic peptides are very small. Here, we show a remarkable difference in the kinetics of TCR interactions with strong agonist ligands at 37 degrees C compared to 25 degrees C. This difference is not seen with antagonist/positive selecting ligands. The interaction at 37 degrees C shows biphasic binding kinetics best des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
194
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(206 citation statements)
references
References 44 publications
12
194
0
Order By: Relevance
“…Another explanation involves the affinity of the TCR for the MHC-peptide complex. Kinetic models of TCR-MHC interaction describe a relationship between T cell activation and the affinity of the TCR for its ligand (33,34). Expression of high TCR affinity ligands is associated with a prolonged interaction with the TCR, which leads to the induction of a Th1 phenotype, anergy, or apoptosis, whereas low affinity ligands are associated with the induction of a Th2 phenotype and T cell anergy (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation involves the affinity of the TCR for the MHC-peptide complex. Kinetic models of TCR-MHC interaction describe a relationship between T cell activation and the affinity of the TCR for its ligand (33,34). Expression of high TCR affinity ligands is associated with a prolonged interaction with the TCR, which leads to the induction of a Th1 phenotype, anergy, or apoptosis, whereas low affinity ligands are associated with the induction of a Th2 phenotype and T cell anergy (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Protocols to identify high avidity T cells would provide an opportunity to analyze in ex vivo assays the interclonal T cell competition during T cell expansion and to sort high avidity T cell clones to be used in adoptive T cell transfer therapy (6). Several factors can influence the avidity of interactions between TCR and MHC class I/peptide complexes, including the density and stability of TCR/ MHC class I peptide complexes (7)(8)(9), the colocalization of TCR and CD8 in the immune synapse (7, 10 -13), and the binding of CD8 molecules (14). Initial reports suggested that the intensity of staining by tetrameric soluble MHC/peptide complexes (tetramers) could be used as a parameter to identify high avidity T cells (15)(16)(17)(18), and more recently it has been shown that stability of tetramer binding to T cell clones could be used to assess the affinity of TCR recognition (19,20).…”
mentioning
confidence: 99%
“…While neither partial agonists nor null peptides interfere with the signaling promoted by the full agonist, antagonist peptides are able to inhibit TCR activation induced by the agonist peptide. Biochemical studies have recently correlated the dissociation rate (k off ) of the TCR-MHC/peptide interaction with the biological activity of APLs (13)(14)(15)(16)(17)(18). Thus, while partial agonists dissociate faster from the TCR than the full agonists, antagonist peptides have even faster dissociation rates than partial agonists.…”
mentioning
confidence: 99%